A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae) - Anker, Arthur (Zootaxa, 2017)
Alpheopsis keijii sp. nov. is described on the basis of material collected between 90 and 487 m in Japan, the Philippines, Papua New Guinea and Réunion Island. The new species belongs to the A. trispinosa species group and is morphologically closest to A. trispinosa (Stimpson, 1860), A. garricki Yaldwyn, 1971, A. shearmii (Alcock & Anderson, 1899), and especially A. africana Holthuis, 1952. Field data indicates that A. keijii sp. nov. may be associated with deep-water sponge grounds. A provisional key to the currently known species of the A. trispinosa group is provided.